(untitled) (inOpera Esercizi di lettura su testi contemporanei, 2025)
This contribution brings to light an unpublished text written by Vittorio Sereni, titled Immagine di Guillaume Apollinaire and currently held in the Vittorio Sereni Archive at Palazzo Verbania in Luino. Hypothetically dating back to the immediate post-Second World War period, this essay is compared to the two other known works by Sereni (published in Gli immediati dintorni, 1962, and in Letture preliminari, 1973), making it potentially the earliest known piece dedicated to the French poet. The curator’s introduction provides a contextualization of the text within the framework of Sereni’s subsequent poetic translations from Apollinaire.